Income distribution policies for faster poverty reduction - Tony Addison; Giovanni Andrea Cornia (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Inequality has risen in many countries over the last two decades, especially in the transition economies, but also in many developing and developed economies. This is disturbing since little progress can be made in poverty reduction when inequality is high and rising. Moreover, contrary to earlier theories of development, high inequality tends to reduce economic growth, and therefore poverty reduction through growth. This paper finds evidence of a concave relationship between inequality and growth: growth can be low (or negative) at low levels of inequality (due to disincentive effects) and low (or negative) at high levels of inequality (due, for instance, to the depressing effect on private investment of the social conflict associated with high inequality). `Traditional' sources of inequality must be addressed through land reform, and more public spending on the human capital of the poor. But new causes of rising inequality must also be tackled by: redesigning stabilization programmes to avoid sharp anti-poor demand compression and to protect pro-poor spending; regulation of privatized enterprises to protect disadvantaged poor consumers; and more pro-poor education investment to offset the tendency of trade liberalization to increase income inequality.
Keywords: D30; I30; O15; 330; income inequality; poverty reduction; economic growth; social conflict; Einkommensverteilung; Armut; Wirtschaftswachstum; Sozialer Konflikt; Welt; Entwicklungsländer